Pemanfaatan Limbah Cair Industri Tahu Sebagai Pupuk Organik Cair (POC) Guna Mendukung Program Lorong Garden (Longgar) Kota Makassar - Sitti Saenab; Mimien Henie Irawati Al Muhdar; Fatchur Rohman; Arifah Novia Arifin (Jurusan Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2018)
The purpose of this research is to know how the utilization of liquid waste of tofu as liquid organic fertilizer to support Makassar city government program. This research is descriptive research which describes the utilization of liquid waste of tofu as liquid organic fertilizer which studied through literature study and direct observation. From the results of field observations and literature studies in the know that the Karang Anyar village has the potential for the development of liquid fertilizer derived from the tofu industry liquid waste. Utilization of liquid fertilizer generated also has great potential in supporting the government program to realize the lorong garden into the center of organic crops because liquid fertilizer that has been produced can be applied to the organic plant in the lorong garden of the new urban village.